Bio-click chemistry: a bridge between biocatalysis and click chemistry. Issue 4 (12th January 2022) - Rodríguez, Diego F.; Moglie, Yanina; Ramírez-Sarmiento, César A.; Singh, Sachin Kumar; Dua, Kamal; Zacconi, Flavia C.
Abstract : This review summarizes chemo/biocatalytic syntheses that combine the highly efficient click chemistry reactions with the advantages of biocatalysis. The concept of bio-click chemistry and its implications are introduced in this review. Abstract : The fields of click chemistry and biocatalysis have rapidly grown over the last two decades. The development of robust and active biocatalysts and the widespread use of straightforward click reactions led to significant interactions between these two fields. Therefore the name bio-click chemistry seems to be an accurate definition of chemoenzymatic reactions cooperating with click transformations. Bio-click chemistry can be understood as the approach towards molecules of high-value using a green and sustainable approach by exploiting the potential of biocatalytic enzyme activity combined with the reliable nature of click reactions. This review summarizes the principal bio-click chemistry reactions reported over the last two decades, with a special emphasis on small molecules. Contributions to the field of bio-click chemistry are manifold, but the synthesis of chiral molecules with applications in medicinal chemistry and sustainable syntheses will be especially highlighted.